Research of influence of the earth’s subsidence outside the loads contour on the stability of the height position of the points of local leveling networks - Dutchyn, Myroslav; Grytsyuk, Tetyana; Bida, Iryna; Dorosh, Liubov; Pylypyuk, Rostyslav; Nychvyd, Mariya (Geodesy and Cartography, 2020)
The influence of static loadings of the foundations of structures in the process of soil compaction of the base on the subsidence of the soil surface and the bench outside the loaded contour is considered in the work. The studies were performed on models of rectangular massive foundations using the method of equivalent soil layer, based on the theory of compaction of linear-deforming half-space. Using this method, the values of the average sedimentation of the models of rectangular foundations were calculated, taking into account all components of normal stresses and lateral soil extension. On the basis of the method of angular points of the equivalent layer, the values of subsidence of the soil surface outside the contour of the foundation models are calculated, depending on the distance from the contour of the foundation, the value of the average subsidence of the foundation and its parameters. To determine the areas of the soil surface most sensitive to the perception of static loads, lines of equal settlements of the soil surface outside the contour of the foundation models are constructed. On the basis of theoretical studies, probable magnitudes of sedimentation of soil benchmarks are calculated, depending on the subsidence of the soil surface and the distance from the contour of the foundation. The probable minimum distance from the contour of the structure to the places of laying of initial soil benchmarks is established to ensure the required accuracy of geodetic observations. The results of the conducted researches may find application in the design of geodetic observations of the settlements and deformations of the foundations of engineering structures and the choice of the locations of local level points.